A snapshot assessment of the diet of Cape fur seals Arctocephalus pusillus pusillus at Ilha dos Tigres, Angola. Issue 4 (17th December 2019) - Winkler, A; Mannheim, S; Childs, A-R; Santos, C; de Beer, C; Smale, MJ; Potts, WM
Abstract : The population of Cape fur seal Arctocephalus pusillus pusillus at Ilha dos Tigres off the coast of southern Angola is expanding. Until now the only available biological information on the population has been its demographic parameters, and this insufficiency has hindered our understanding of the population's ecology. The current study aimed to describe the diet of this northernmost population of the subspecies, based on a once-off sampling opportunity. The diet was described using scat analysis and hard-part identification from scats collected in July 2014. Small pelagic fishes ( Trachurus spp., Engraulis encrasicolus and Sardinops sagax ) were the numerically dominant prey items, conforming with the findings of studies conducted on other Cape fur seal colonies. Although not numerically dominant, cephalopods were dominant in terms of mass.